2t - 7 = 3t - 10
any one tell me
Answers
Answered by
2
Answer:
= 2t - 7 = 3t - 10
= t = 10 - 7
= 3
Hope this helps u ❤️✨❤️✨❤️✨❤️
pls follow kar do plz ☺️☺️☺️☺️☺️☺️
Answered by
0
Step-by-step explanation:
please followup me and make me branlist
Attachments:
![](https://hi-static.z-dn.net/files/def/e3ae2b6d357e5f128bbcac7156de580a.jpg)
![](https://hi-static.z-dn.net/files/dd3/b3dd0fb9d1afa38f81bd5f3a127fd2a7.jpg)
Similar questions
Social Sciences,
4 months ago
Physics,
4 months ago
Math,
4 months ago
Math,
9 months ago
Computer Science,
9 months ago